Roquin targets mRNAs in a 3′-UTR-specific manner by different modes of regulation - Essig, Katharina; Kronbeck, Nina; Guimaraes, Joao C.; Lohs, Claudia; Schlundt, Andreas; Hoffmann, Anne; Behrens, Gesine; Brenner, Sven; Kowalska, Joanna; Lopez-Rodriguez, Cristina; Jemielity, Jacek; Holtmann, Helmut; et al. (Nature communications, 2018)
The RNA-binding proteins Roquin-1 and Roquin-2 redundantly control gene expression and cell-fate decisions. Here, we show that Roquin not only interacts with stem–loop structures, but also with a linear sequence element present in about half of its targets. Comprehensive analysis of a minimal response element of the Nfkbid 3′-UTR shows that six stem–loop structures cooperate to exert robust and profound post-transcriptional regulation. Only binding of multiple Roquin proteins to several stem–loops exerts full repression, which redundantly involved deadenylation and decapping, but also translational inhibition. Globally, most Roquin targets are regulated by mRNA decay, whereas a small subset, including the Nfat5 mRNA, with more binding sites in their 3′-UTRs, are also subject to translational inhibition. These findings provide insights into how the robustness and magnitude of Roquin-mediated regulation is encoded in complex cis -elements. Roquin targets are known to contain two types of sequence-structure motifs, the constitutive and the alternative decay elements (CDE and ADE). Here, the authors describe a linear Roquin binding element (LBE) also involved in target recognition, and show that Roquin binding affects the translation of a subset of targeted mRNAs.